2013
DOI: 10.1002/grl.50384
|View full text |Cite
|
Sign up to set email alerts
|

Environmental controls of frost cracking revealed through in situ acoustic emission measurements in steep bedrock

Abstract: [1] Frost cracking, the breakdown of rock by freezing, is one of the most important mechanical weathering processes acting on Earth's surface. Insights on the mechanisms driving frost cracking stem mainly from laboratory and theoretical studies. Transferring insights from such studies to natural conditions, involving jointed bedrock and heterogeneous thermal and hydrological properties, is a major challenge. We address this problem with simultaneous in situ measurements of acoustic emissions, used as proxy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 34 publications
(47 reference statements)
6
107
0
1
Order By: Relevance
“…Vegetation can lower ground temperatures by shading and evapotranspiration, and in other places exert a warming influence by retaining snow cover in wind-exposed areas (Hinkel and Hurd, 2006;Kokelj et al, 2010). Ground material further differentiates subsurface temperature, and some substrates such as an organic layer (Burn and Smith, 1988;Goodrich, 1982) or coarse blocks (Delaloye and Lambiel, 2005;Gruber and Hoelzle, 2008) result in a relative lowering of subsurface temperatures. Local drainage characteristics affect ground temperatures through latent heat and the effect of water saturation on thermal conductivity contrasts between frozen and thawed soil (Endrizzi et al, 2014) and through differing albedo of wet and dry soil (Ma et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation can lower ground temperatures by shading and evapotranspiration, and in other places exert a warming influence by retaining snow cover in wind-exposed areas (Hinkel and Hurd, 2006;Kokelj et al, 2010). Ground material further differentiates subsurface temperature, and some substrates such as an organic layer (Burn and Smith, 1988;Goodrich, 1982) or coarse blocks (Delaloye and Lambiel, 2005;Gruber and Hoelzle, 2008) result in a relative lowering of subsurface temperatures. Local drainage characteristics affect ground temperatures through latent heat and the effect of water saturation on thermal conductivity contrasts between frozen and thawed soil (Endrizzi et al, 2014) and through differing albedo of wet and dry soil (Ma et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…(c) Ice wedges on slopes are likely underestimated in their frequency of occurrence as their micro-topographic signature is suppressed by soil movement (Mackay, 1990). In bedrock permafrost, fractures often contain large amounts of ice, affecting slope stability and flow of water Ravanel et al, 2010), and the slow formation of ice-rich layers by segregation appears plausible (Girard et al, 2013). The freezing and melting of ice in soil or rock occurs progressively over a range of temperatures below 0 • C and the high latent heat of fusion often subdues temperature change in frozen soil (Romanovsky and Osterkamp, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Minor concentrations of MS events occur during the summer months when air and rock temperatures temporarily rise above 0°C. In this sense, recent field observations on the North-eastern ridge of Matterhorn, the Hörnligrat , and the Jungfraujoch (Girard et al 2013) show that: (i) cleft movements during the cold season are caused by thermo-mechanical forcing and are reinforced by cryogenic processes during the freezing period, while, (ii) in summer the main movements originate from hydro-thermally induced strength reduction (increase of water pressure) in rock fractures containing perennial ice. …”
Section: Microseismic and Temperature Data Analysismentioning
confidence: 98%
“…The approaches include the analysis of slope failure inventories, case histories and trigger mechanisms, and Huggel et al (2013) concluded that these are promising avenues for detection studies. Gruber (2013) notes the difficulties of understanding lowfrequency and high-magnitude events, such as landslide hazards in cold regions that may be intensified by progressive and nonlinear changes in the periglacial environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hyper-arid regions, for instance, are too dry to promote frost cracking (Hall et al, 2002) and polar deserts sustain the slowest denudation rates on Earth (Portenga and Bierman, 2011). In less extreme environments it is worth noting that water need not be present all year to promote frost cracking (Girard et al, 2013). For negative MAT environments, water must be available at the surface in warm periods (e.g.…”
Section: Water Availabilitymentioning
confidence: 99%